UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN IPAS MELALUI PENGGUNAAN MODEL PROBLEM BASED LEARNING DI KELAS 4 SD NEGERI KUANINO - Umar, Ulfah Mualifah; Ande, Andreas; Adoe, Treesly Y. Normin (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to improve the learning outcomes of students in Natural and Social Sciences (IPAS) subjects through the application of the Problem based learning (PBL) learning model in grade IV of SD Negeri Kuanino. The research method used is Class Action Research (PTK) which is carried out in two cycles. The subjects of this study are 22 students. Data collection techniques include observation of teacher and student activities, as well as learning outcome tests. The results showed a significant increase in learning outcomes and learning activities. In the first cycle, the students' learning completeness reached 59.09%, and increased to 100% in the second cycle. Teachers' activities in the first cycle obtained an average observation score of 66.91% (adequate category), increasing to 89% (very good category) in the second cycle. Student activity also increased from 67.4% (adequate category) in the first cycle to 85.5% (very good category) in the second cycle. These findings show that the application of the Problem based learning model is effective in improving the learning outcomes of social studies and student learning activities, especially in the material "Indonesiaku Kaya Budaya". The PBL model is worthy of being used as an innovative learning strategy that encourages activeness, collaboration, and in-depth understanding of concepts in elementary schools.